PENGEMBANGAN STRATEGI PEMBELAJARAN BIOLOGI UNTUK MENINGKATKAN KEBERMAKNAAN KONSEP DITINJAU DARI KEMAMPUAN INGATAN DAN KETELITIAN KERJA - ALVI ROSYIDI (Bioedukasi: Jurnal Pendidikan Biologi, 2004)
The aim of this research were to study the influence of using the scientific method on these following aspects: (1) The improvement of concept of 4 ,h semester’s subject of Biological Education, FKIP UNS, (2) Whether the memory capabilities can be used as a predictor or not, (3) The Carefulness can be used as a significant predictor and (4) contribution of each predictor on that improvement.Descriptive-quantitative research methods with expofacto were used, t test and regression were used to analyze the data. Data are collected by test method and it’s collection with two design; comparative and correlative on 30 samples of the 4 '* semester’s student.The result showed that the scientific method could raise the improvement of subject concept only slightly with no statistical differences. Beside, there is a positive correlation between either the memory capabilities or carefulness and the improvement the concep